EVALUASI PENATAAN KAWASAN TERMINAL SIMPANG AUR KUNING KOTA BUKITTINGGI - Netti, Nelma; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Terminal Simpang Aur Kuning of Bukittinggi city was included into class A type and build in 1983 next to Aur Kuning Market. At the beginning it had been functioned as it should be. However due to economic progression and street vendors activities, market expansion had become unavoidable. Therefore lesser spaces of terminal were remained. Meanwhile at the outside area of terminal had been build a kind of shadow terminal which taken a part of the road in front of SMA N 3 Bukittinggi. Based on those situations, researcher was attracted to study the area management of Terminal Simpang Aur Kuning of Bukittinggi city.This research was conducted based on theories evaluation of William N Dunn. This theory study a policy based on six criteria of evaluation namely: affectivity, efficiency, adequacy, equalization , response and precision. This research was aimed to evaluate area management of Terminal Simpang Aur Kuning and all affecting factor. It used qualitative method and data studied descriptively. Data collection was carried out with interview, observation and documentation based on purposive sampling method and analyzed by triangulation technique.The research result shown that area management of Terminal Simpang Aur Kuning of Bukittinggi city was not properly done and need to be improved with terminal expansion method. By considering limited area availability, local government was hoped to evict certain market (stores) building on terminal land, improving services by making certain needed infrastructures, improving human resources competency, good coordination with stake holders in order to reach good terminal management.Key words: Policy, Evaluation, Terminal